Climate Change and Water Governance: Decision Making for Individual Vineyard Owners in Global Wine Regions - Upton, Erin; Nielsen-Pincus, Max (Frontiers in Climate, 2021)
This study investigates the institutional, social, and ecological dynamics that influence regional water governance and individual vineyard owners' decisions-making in global wine regions. Global wine grape production has grown steadily over the past twenty years, and climate change has emerged as a driver of transformation in wine regions resulting in a range of impacts. Changes to the climate are anticipated to accelerate in the future and present a number of challenges for wine regions; including risks to human systems, e.g., agriculture, labor, and economics, as well as ecological systems, e.g., surface and groundwater. Water is a critical resource for environmental and economic sustainability in wine regions, and vulnerability to freshwater resources in wine producing regions is expected to increase as wine regions experience climate extremes like heat and drought. We use the Institutional-Social-Ecological Dynamics (ISED) framework to help understand individual vineyard owner decision making about water management within the context of institutional, social, and ecological systems. We ask how the relationships between these systems impact outcomes for individual grape farmers adapting to climate challenges. Our empirical research uses document review and interviews with vineyard owners, planners, and natural resource managers in wine regions in Oregon, USA and Tasmania, Australia as a means to explore climate vulnerabilities and adaptation approaches. Subsequently we focus on an example vignette in each region to better understand individual decision-making at the farm scale within the unique institutional, social and ecological contexts identified in each region. Our cases highlight the finding that entrenched institutional regimes, in the context of ecological variability contribute to a social unevenness in access to water. Landowner conflict over water resources is likely to increase in the context of a hotter, drier climate in regions with wine industry growth. Individual vineyard owners have a range of attitudes and approaches to climate change planning and management; and adaptation around water is dependent on both economic resources and social values. Lessons from the individual farm scale help to inform broader implications of how institutional, social, and ecological drivers influence opportunities or barriers to the implementation of climate change adaptation practices in wine regions.